Synthesis and Characterization of Dibutyltin(IV) Comp)exes of Substituted Catechol - Farina, Yang; Baba, I.; Othman , A. H.; Fadzilah, N.; Mohamed, R. (Universiti Putra Malaysia Press, 1998)
The complexes of dibutyltin (IV) with anions of 4-tert-buty1catechol, 4chlorocatechol, 4-nitrocatechol, 3,4-dihydroxybenzaldehyde, and 3,4dihydroxybenzoic acid were synthesized by reacting dibutyltin (IV) oxide with the corresponding free ligands. The isolated complexes were characterized by elemental analysis and spectroscopic methods such as infrared, lH and 13C NMR. Complex formation between the dibutyltin(IV) moiety and the anions of 4-tert-butylcatechol, 4-chlorocatechol, 4-nitrocatechol and 3,4dihydroxybenzaldehyde takes place with chelation at the o-hydroxy positions. However, results of analysis carried out on the dibutyltin (IV) complex of 3,4dihydroxybenzoic acid showed that the carboxylic group is also involved in chelate formation. Results of the lethality bioassay on the brine hrimp (Artemia salina) indicated that all the complexes have biological activity but only the 4tert- buty1catechol complex was able to cleave D A (plasmid pBR 322).